Evidence of impaired H-reflex and H-reflex rate-dependent depression in diabetes, prediabetes and obesity: a mini-review - Kababie-Ameo, Rebeca; Gutiérrez-Salmeán, Gabriela; Cuellar, Carlos A. (Frontiers in Endocrinology, 2023)
Diabetes Mellitus is a public health problem associated with complications such as neuropathy; however, it has been proposed that these may begin to develop during prediabetes and may also be present in persons with obesity. Diabetic peripheral neuropathy is the presence of signs and/or symptoms of peripheral nerve dysfunction in people living with diabetes, which increases the risk of developing complications and has a deleterious impact on quality of life. As part of the therapeutic protocol for diabetes, screening tests to identify peripheral neuropathy are suggested, however, there are no recommendations for people with prediabetes and obesity without symptoms such as pain, numbness, or paresthesias. Moreover, clinical screening tests that are usually used to recognize this alteration, such as tendon reflex, temperature sensation, and pressure and vibration perception, might be subjective as they depend on the evaluator’s experience thus the incorrect application of these tests may not recognize the damage to small or large-nerve fibers. Recent evidence suggests that an objective study such as the impairment of the rate-dependent depression of the H-reflex could be used as a biomarker of spinal disinhibition and hence may provide more information on sensorimotor integration.